Clinical Features in Juvenile-Onset Ankylosing Spondylitis Patients Carrying Different B27 Subtypes. (26th July 2015) - Mou, Yikun; Zhang, Pingping; Li, Qiuxia; Lin, Zhiming; Liao, Zetao; Wei, Qiujing; Gu, Jieruo
Abstract : Background . Ankylosing spondylitis (AS) is a common rheumatic disease and is characterized by inflammation of the axial skeleton. HLA-B27 is strongly associated with AS. Juvenile-onset AS (JAS) with disease onset before 16 years of age differs from adult-onset AS (AAS) in many respects. Objective . To compare the clinical features in JAS with different B27 subtypes and analyze the differences between JAS and AAS. Methods . 145 JAS and 360 AAS patients were included. The demographic data, clinical manifestations, laboratory markers, Bath AS indices, and B27 subtypes were recorded. Results . Peripheral arthritis, enthesitis, BASDAI, ESR, and CRP were significantly higher in JAS patients with HLA-B * 2704 than those with B27-negative. Enthesitis and ESR were significantly higher in patients with HLA-B * 2705 than those with B27-negative. The onset age of HLA-B * 2715 group was much earlier than the other groups. The peripheral arthritis, enthesitis, and hip joint involvement in JAS with HLA-B * 2704 were significantly higher than those in AAS with HLA-B * 2704. Conclusion . JAS with different B27 subtypes had similar features in most of manifestations; JAS and AAS patients with the same subtype could have distinctive courses. Early diagnosis, hip detection, and control of systemic active inflammation in JAS patients will be helpful for improving the prognosis.